1984
DOI: 10.1159/000199012
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Cell Proliferation and Enteroglucagon Response following Small Bowel Resection in the Rat

Abstract: Gut resection triggers off a complex series of adaptive changes in the remaining bowel. There is evidence that these are partly mediated by hormonal factors and enteroglucagons have been proposed as candidates for this role. It is uncertain, however, whether plasma enteroglucagon concentrations rise quickly enough to be involved in the rapid initial response or are persistent enough for chronic maintenance. Plasma concentrations of enteroglucagon were therefore estimated at varying times following gut resectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Physiologically, SCFAs are a logical mediator of trophic gastrointestinal hormones (i.e., PGDPs) and ileal adaptation because they are produced distally within the gastrointestinal tract in response to malabsorbed substrate. Many studies have established a strong relation between cellular proliferation and elevated amounts of proglucagon mRNA and PGDPs [97,98,[102][103][104]. Taylor et al [100] reported that after intestinal resection, proglucagon expression increased threefold, peaking 2 days after surgery and declining thereafter.…”
Section: Short-chain Fatty Acids (Scfas)mentioning
confidence: 99%
“…Physiologically, SCFAs are a logical mediator of trophic gastrointestinal hormones (i.e., PGDPs) and ileal adaptation because they are produced distally within the gastrointestinal tract in response to malabsorbed substrate. Many studies have established a strong relation between cellular proliferation and elevated amounts of proglucagon mRNA and PGDPs [97,98,[102][103][104]. Taylor et al [100] reported that after intestinal resection, proglucagon expression increased threefold, peaking 2 days after surgery and declining thereafter.…”
Section: Short-chain Fatty Acids (Scfas)mentioning
confidence: 99%
“…An enteroglucagon secreting tumour was associated with increased height of the villi and increased mucosal thickness which was reversed after tumour removal.`Subsequently, raised circulating concentrations of enteroglucagon have been reported in various clinical conditions and experimental animal models being associated with an increase in the intestinal epithelial cell turnover which all had in common that they were characterised by an increased food supply to the intestine.5 Especially the adaptive hyperplastic response of ileal remnants after proximal bowel resection are paralleled by an increase in plasma and tissue concentrations of enteroglucagon both showing a close relationship to the extent of the small intestine being resected." 94 In order to gain additional insight into the putative role gut GLI-I of acting as an enterotrophic regulatory peptide we investigated two different experimental conditions which are known to induce intestinal hyperplasia not being associated with an increase in the nutritional load of the intestine: (a) germ free rats were conventionalised with a thermoduric flora and were held thereafter as open conventional animals. Four weeks after conventionalisation the ileal mucosa exhibited a significant increase of mitotic activity and crypt length accompanied by unchanged basal EG plasma concentrations and decreased tissue levels of EG in the contaminated group.…”
Section: Regulation Of Mucosal Growth In Relation To Gastrointestinalmentioning
confidence: 99%